Strengthening Work Culture to Enhance Student Competence in Vocational High Schools: A Comparative Case Study - Ria Setiawati; Hanafiah Hanafiah (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the management of strengthening work culture to enhance student competence in vocational high schools amid technological and industrial advancements. Teachers must continually upgrade their skills for innovative learning, supported by work culture features such as attitudes, skills, knowledge, methods, media, modules, programs, resources, facilities, and budgets—preparing students for business/industry. Using a qualitative descriptive approach, data from interviews, observations, and documentation of implementing schools reveal that effective strategies—planning, organization, implementation, and evaluation—boost competence. Mentoring, periodic reviews, and roles of teachers (role models), principals (strategic managers), staff (operational support), students (active participants), and industry partners (internship sites) amplify impacts. Strengthening work culture offers a strategic solution for industry-ready graduates. Recommendations include school and government policies to promote these programs.